+0

# 5j+6c=32

0
53
2

5j+6c=32

1j+3c=10

Guest Oct 18, 2017

#2
+17655
+1

If you are to solve this problem for j and for c, multiply the second equation by 2 and subtract from the first equation.

5j + 6c  =  32                    --->     5j + 6c   =  32

1j + 3c  =  10     --->   x2   --->     2j + 6c  =  20

Subtract                            --->     3j           =  12

Divide by 3                       --->                  j  =  4

Substitute 4 for j in the second equation:  1j + 3c  =  10     --->     1(4) + 3c  =  10     --->     4 + 3c  =  10

Subtract 4 from both sides                                              3c  =  6

Divide by 3                                                                        c  =  2

A solution of this set of equations is:  c = 2  and  j = 4.

geno3141  Oct 18, 2017
Sort:

#1
+91038
0

Melody  Oct 18, 2017
#2
+17655
+1

If you are to solve this problem for j and for c, multiply the second equation by 2 and subtract from the first equation.

5j + 6c  =  32                    --->     5j + 6c   =  32

1j + 3c  =  10     --->   x2   --->     2j + 6c  =  20

Subtract                            --->     3j           =  12

Divide by 3                       --->                  j  =  4

Substitute 4 for j in the second equation:  1j + 3c  =  10     --->     1(4) + 3c  =  10     --->     4 + 3c  =  10

Subtract 4 from both sides                                              3c  =  6

Divide by 3                                                                        c  =  2

A solution of this set of equations is:  c = 2  and  j = 4.

geno3141  Oct 18, 2017

### 8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details